THE CONSTRUCTION OF POLITICAL SYMBOLICM OF INDIVIDUAL POLITICAL ACTION: CASE STUDY ANALYSIS IN THREE ISLAMIC BASED POLITICAL PARTIES IN GOWA DISTRICT - Sastrawati, Nila (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2019)
This paper is the research result that focuses on the construction of political symbols in encouraging individual political action in the United Development Party, the National Mandate Party, and the National Awakening Party in Gowa District. This research is a qualitative research, using the sociological phenomenology approach. The results shows that religious symbolism in the three Islamic-based political parties in Gowa encourage individual political actions in two ways, namely; objective and subjective realities of political parties, and objective and subjective realities of individuals towards their social environment